EFEK DARI COUNTRY OF ORIGIN DAN PENGETAHUAN PRODUK PADA EVALUASI PRODUK DAN NIAT PEMBELIAN PRODUK SEPEDA MOTOR - Dwi Hastjarja Kustijana, Ratna Susanti & (Universitas Slamet Riyadi, 2010)
ABSTRACT This research is about effect from country of origin (COO) and knowledge of product at product evaluation and purchase intention purchasing of motorbike. Population is in society of Jebres, sample is 100 respondent. Technique sampling with non-probability that is convenience sampling. This research problem: (1) COO have influence to product evaluation and purchase intention, (2) knowledge have influence to product evaluation and purchase intention, (3) product evaluation have influence to purchase intention, and (4) COO have mediate product evaluation and knowledge of product to purchase intention. Analysis use covariance analysis (ancova), while to test mediate influence evaluate product between COO and knowledge of product to purchase intention use path analysis. Result of path analysis show all variable have significance value < 0,05. Thereby COO and knowledge have direct influence, knowledge have direct influence at purchase intention and also mediated evaluate product. Conclusion of this research that five hypothesis supported and two hypothesis is not supported. This caused by consumer have objective knowledge and low subjective in purchasing of motorbike is influenced by COO. While COO and knowledge of product have direct influence to purchase intention and also mediated evaluate product. Suggestion can be passed to otomotif producer better remain to maintain and try to improve COO image in consumer view and company continue to improve knowledge storey level consumer by giving information about product. Keywords: country of origin, knowledge of product, product evaluation, purchase intention